Home-based medication safety: constructing health education for community-dwelling older adults with chronic diseases in China - Yuting Yang; Yongwei Yang; Miao Yao; Ting Lin (Annals of Medicine)
Background Chinese older adults with chronic diseases often require long-term medication use. While medication safety education can improve health outcomes and mitigate risks, existing programs lack systematic and comprehensive frameworks. This study aimed to develop Delphi-based consensus content to enhance home-based medication safety education for this population.Methods A two-round Delphi study was conducted from June to August 2022 with 16 experts in clinical medicine and pharmacy (87.50% holding senior professional titles). Expertise levels included four experts with >10 years, five with >20 years, and seven with >30 years of experience. Using the WHO’s 5 Moments for Medication Safety framework, a three-part questionnaire was designed: (a) sociodemographics; (b) expert familiarity and importance ratings of indicators; (c) evaluation form for home-based medication safety education. Key metrics included response rates, expert authority coefficient (Cr), coefficient of variation (CV), and Kendall’s W for consensus.Results Response rates were 80.00% (Round 1) and 100% (Round 2), meeting validity thresholds. High expert authority was demonstrated (Cr: 0.917 and 0.933). Consensus improved across rounds (CV: 0.22 and 0.13; Kendall’s W: 0.354 and 0.257, both p < 0.001). After iterative revisions and panel discussions, a finalized system comprising five first-level and 22 second-level items was established.Conclusion We specially designed a content system for medication safety education for older adults. Future researchers could focus on implementing this content system to provide medication safety education for patients.